Penerapan Teknologi Augmented Reality Untuk Pembelajaran Gerbang Logika Pada Mata Pelajaran Sistem Komputer - Mochammad Machlul Alamin; Hendrawan Armanto; Indra Maryati (STMIK Budi Darma, 2020)
Logic Gate is one of the materials in the subject of Computer Systems at the level of SMK in class X. However, until now the learning media only uses textbooks, power point slides and manual simulations using blackboards. While the material about logic gates is very difficult if it is not directly simulated because it is directly related to the interaction of inputs and outputs at each logic gate. During the use of textbooks and manual simulation media students find it difficult to understand the material about this logic gate. The advantage of learning that utilizes augmented reality is an attractive display and displays 3D logic gate objects and input buttons that can be used to interact directly and the output is also in the form of 3D lamp objects, with this augmented reality technology will be very helpful and useful for simulating the gate logic is directly and easily understood by students. 3D logic gate animations are created using the 3D Blender application and the Augmented Reality process is created using the Unity and Vuforia SDK Library. This logic gate learning application has been applied to two classes, namely the control class and the experimental class. From the results of the Pre Test and Post Test that have been done, the control class has a 22.0% increase in percentage, while the experimental class has a 33.4% increase in percentage. Thus the learning application that utilizes Augmented Reality technology can be applied as a medium for learning logic gates at the vocational level of class X